Pengaruh Konten Fashion pada Akun Media Sosial Influencer Terhadap Perilaku Konsumtif di Kalangan Pengguna TikTok dan Instagram - Siregar, Desi Asnita; Harahap, Nursapia (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The purpose of this research is to see the effectiveness of exposure to @helwabasheel account fashion content on TikTok and Instagram on consumptive behavior. The method used in this research is a Quantitative approach. The population used is followers of @helwabasheel's TikTok and Instagram accounts. The sample taken by the researcher amounted to 50 respondents who were active followers on the TikTok and Instagram @helwabasheel accounts using purposive sampling techniques. The research data collection was carried out using a questionnaire with a Likert scale using indicators of effectiveness and consumptive behavior. Data analysis techniques using SPSS 22, with multiple linear regression analysis tests accompanied by t tests and F tests. The results of the analysis show that the coefficient of determination of the effectiveness of exposure to Tiktok and Instagram fashion content on consumptive behavior is 77.5%, while the remaining 22.5% is influenced by other factors, and is not included in this study. While the t test value of 4.119 with a significance level of 0.000 < 0.05, this proving that the effectiveness of exposure to Tiktok content (X1) has a positive effect on consumptive behavior. And also the t test result of 4.068 with a significance level of 0.000 < 0.05, this proving that the effectiveness of exposure to Instagram content (X2) has a positive effect on consumptive behavior. A very effective platform for consumptive behavior on @helwabasheel accounts is TikTok.